Prevalence of Drug Resistance Mutations and Non-B Subtypes in Newly Diagnosed HIV-1 Patients in Denmark - B. Jørgensen, Louise; B. Christensen, Marianne; Gerstoft, Jan; R. Mathiesen, Lars; Obel, Niels; Pedersen, Court; Nielsen, Henrik; Nielsen, Claus (Scandinavian journal of infectious diseases, 2003)
The aim of this study was to monitor the prevalence of drug resistance mutations in newly diagnosed HIV-1 positive individuals in Denmark. In addition we assessed the prevalence of non-B subtypes based on phylogenetic analysis of the pol gene. Plasma samples from 104 newly diagnosed HIV-1 positive patients were obtained in the year 2000. The entire protease gene and 320 amino acids of the reverse transcriptase gene were genotyped. Sequences were obtained from 97 patients. No subjects displayed primary resistance mutations in the protease gene, whereas all carried 1 or more secondary mutations. Resistance mutations in the RT-gene associated with NRTI-resistance were found in 1 patient, who was infected with zidovudine resistant HIV-1 harbouring the M41L mutation in combination with T215S and L210S. The T215S mutation has been showed to be associated with reversion of zidovudine resistance. The T215S mutation was found in 1 additional patient. The subtype distribution was subtype B 59%, C 18%, A 8%, CRF02_AG 5%, CRF01_AE 4%, D 3% and G 2%. We found 2 patients (2%) with mutations associated with resistance in the RT-gene and none in the protease gene indicating a low prevalence of resistant HIV-1 in Denmark in the year 2000.